Evaluation of the Family Integrated Care model of neonatal intensive care: a cluster randomized controlled trial in Canada and Australia. Issue 1 (December 2015) - O'Brien, Karel; Bracht, Marianne; Robson, Kate; Ye, Xiang; Mirea, Lucia; Cruz, Melinda; Ng, Eugene; Monterrosa, Luis; Soraisham, Amuchou; Alvaro, Ruben; Narvey, Michael; Da Silva, Orlando; et al.
Abstract Background Admission to the neonatal intensive care unit (NICU) may disrupt parent-infant interaction with adverse consequences for infants and their families. Several family-centered care programs promote parent-infant interaction in the NICU; however, all of these retain the premise that health-care professionals should provide most of the infant's care. Parents play a mainly supportive role in the NICU and continue to feel anxious and unprepared to care for their infant after discharge. In the Family Integrated Care (FICare) model, parents provide all except the most advanced medical care for their infants with support from the medical team. Our hypothesis is that infants whose families complete the FICare program will have greater weight gain and better clinical and parental outcomes compared with infants provided with standard NICU care. Methods/Design FICare is being evaluated in a cluster randomized controlled trial among infants born at ≤ 33 weeks' gestation admitted to 19 Canadian, 6 Australian, and 1 New Zealand tertiary-level NICU. Trial enrollment began in April, 2013, with a target sample size of 675 infants in each arm, to be completed by August, 2015. Participating sites were stratified by country, and by NICU size within Canada, for randomization to either the FICare intervention or control arm. In intervention sites, parents are taught how to provide most of their infant's care and supported by nursing staff, veteran parents, a program coordinator, and education sessions. In control sites standard NICU care is provided. The primary outcome is infants' weight gain at 21 days after enrollment, which will be compared between the FICare and control groups using Student'st -test adjusted for site-level clustering, and multi-level hierarchical models accounting for both clustering and potential confounders. Similar analyses will examine secondary outcomes including breastfeeding, clinical outcomes, safety, parental stress and anxiety, and resource use. The trial was designed, is being conducted, and will be reported according to the CONSORT 2010 guidelines for cluster randomized controlled trials. Discussion By evaluating the impact of integrating parents into the care of their infant in the NICU, this trial may transform the delivery of neonatal care. Trial registration NCT01852695, registered December 19, 2012